A Hierarchical Model of Organizational Identification (Journal of Organizational Psychology, 2017)
This research study examined the organizational identification process in an organization whose identity claims appeared to be congruent and mutually reinforcing. The study sought to understand members’ identification with each of the identity claims or a subset of the claims over time. A qualitative case study design was employed to understand the individual nature of the identification process. Results showed that as identification emerged, participants responded to a set of multiple identity claims in a hierarchical manner. This study helps foster an understanding of the process of member choice to identify with organizational claims and the shifting hierarchy of organizational identity claims in the process.
Keywords: Organizational Psychology; Hierarchical